DEVELOPMENT OF TERMINOLOGICAL SUBSET FOR PEOPLE WITH COVID-19 SEQUELAE. - Batista Ferreira, Lucas; Lima Lopes, Donátila Cristina; de Menezes, Harlon França; Ferreira de Sousa, Paulino Artur; de Medeiros Dantas, Ana Livia; da Costa Prado, Nanete Caroline; Holanda de Almeida, Ingridy Thaís; Rosendo da Silva, Richardson Augusto (Texto & Contexto Enfermagem, 2022)
Objectives: to develop a terminological subset of the International Classification for Nursing Practice (ICNP) for people with covid-19 sequelae.® Method: methodological study, which followed the steps: Identification of the relevant terms contained in the literature related to Covid-19 sequelae; Cross-mapping of the terms identified in the review with the terms of the classification; Construction of the statements of diagnoses, outcomes and nursing interventions and mapping of the constructed statements; Content validation of the statements by specialist nurses; and Structuring of the subset based on Roy's Adaptation Model. For data analysis, the Content Validity Index was used, and the statements with Content Validity Index were validated ≥ 0.80. Content validation was performed by 28 specialist nurses. Results: 178 statements of nursing diagnoses/outcomes were constructed, with 450 nursing intervention statements. After content validation, a quantity of 127 diagnoses/outcomes and 148 nursing interventions were obtained, which comprised the terminological subset proposed in the study. Conclusion: the validated statements that make up the terminological subset with greater predominance were those outlines in the physiological adaptive mode. However, the repercussions on the spiritual, social and personal dimensions are also highlighted.